Pelatihan Pembuatan Pupuk Kompos Menggunakan Teknologi EM4 di Desa Kidang Kabupaten Lombok Tengah - Siti Rabiatul Fajri; Farida Fitriani; Titi Laily Hajiriah; Sucika Armiani; Akhmad Sukri (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This community service activity aims to improve the ability of the people of Kidang Village in making compost using EM4 technology. This activity is intended for farmer groups, village heads and youth clubs. The method of implementing this service includes the coordination of activities, preparation of tools and materials, implementation and demonstration. This activity is carried out by providing material and how to make compost with EM4 technology. Next is the demonstration using the tools and materials provided previously. In this activity, the training participants were very enthusiastic in participating in the activity until it was finished. There is a positive response so that the activities are held in each hamlet. It is hoped that the delivery of material can be obtained thoroughly by all the people of Kidang Village. In addition, activities like this can be continued to the mass production stage, so that in the future it is expected that Kidang Village has its own fertilizer products that can be traded to increase the income of its people.